Nuclear Capacity Auctions - Sven-Olof Fridolfsson; Thomas Tangerås (Research Institute of Industrial Economics (IFN), 2011)
We propose nuclear capacity auctions as a means to improve the incentives for investing in nuclear power. A properly designed auction would (i) allocate the license to the most efficient bidder; (ii) sell the license if and only if new nuclear power was socially optimal. In particular, capacity auctions open the market for large-scale entry by outside firms. Requiring licensees to sell a share of capacity as virtual power plant contracts increases auction efficiency by softening incumbent producers incentive to bid for market power. Our motivating example is Swedens recent decision to allow new nuclear power to replace old reactors.
Keywords: D44; L12; Q48; 330; Capacity auctions; investments; market power; nuclear power; virtual power plants; Kernenergie; Auktion; Produktionskapazität; Marktmacht; Schweden